The ESRB at 1 - Hermann Remsperger; Stephen G. Cecchetti; Stefan Ingves; Alberto Giovannini; Jens Weidmann; Alexandros Vardoulakis; Stefano Neri; Jürgen Stark; Elod Takáts; Christian Upper; Claudia M. Buch; Sandra Eickmeier; et al. (SUERF - The European Money and Finance Forum, 2012)
SUERF – The European Money and Finance Forum, the Deutsche Bundesbank and the Institute for Monetary and Financial Stability (IMFS) took the opportunity of the first anniversary of this new institution to organise a joint conference in Berlin on 8-9 November 2011. The purpose of this event was to take stock of first experiences with the ESRB; to discuss current issues in the field of macroprudential supervision, including the integration of macro-financial elements into macroeconomic models, the measurement and indicators of systemic risk, macroprudential tools and their effectiveness; and to identify forthcoming challenges for the ESRB and macroprudential supervision at large. This SUERF Study forms the conference proceedings from the event, with the chapters being a selection of the papers and speeches presented at the event.
Keywords: E32; E44; E5; E52; E58; F33; G21; G28; K20; K22; 330; ESRB; systemic risk; financial reform; monetary policy; macroprudential policy; central banking; financial regulation; financial intermediation; microeconomic bank risk; deleveraging; creditless recoveries; credit crunch; credit cycles; financial crises; financial dependence; Finanzkrise; Bankenaufsicht; Kreditrisiko; Systemrisiko; Spillover-Effekt; Finanzmarktregulierung; EU-Staaten